The effect of customer experience on repurchase intention with variety seeking as variable moderation at 4-star hotels - Abrian, Youmil; Adrian, Arif (Universitas Negeri Padang, 2021)
This research aims to determine the influence of customer experience on repurchase intention with variable moderation of variety seeking. The statistical analysis used is moderated analysis regression. The selection of 4-star hotels due to the standard of star hotels pays attention to the increasingly varied needs of consumers. The target population in this study was hotel guests who had stayed at a 4-star hotel in Padang. A simple random sampling technique is used with 286 samples, in obtaining the data a questionnaire with a Likert scale. From the results of the study obtained the influence of variable customer experience had a significant positive effect on the repurchase intention, with a significance value of 0,000<0.05 and had an influence contribution of 4.5%, with a regression coefficient of 0.125. While variety-seeking variables have a significant negative effect on repurchase intention with a significance value of 0<0.05, and have an influence contribution of 6%, with a regression coefficient of -0.197. From the results of moderation regression obtained variety seeks to moderate the influence of customer experience on repurchase intention negatively with the significance of 0,000<0.05, and has a regression coefficient of -0.537 with an influence contribution of 8.7%.